Preferensi Peternak Terhadap Desain Produk Vaksin Flu Burung (POULTRY FARMER PREFERENCES ON THE DESIGN AVIAN INFLUENZA VACCINE PRODUCT) - Syamsidar, Syamsidar; Munandar, Jono Mintarto; Cahyadi, Eko Ruddy; Kusumastuti, Aprilia (Jurnal Veteriner; Vol 19 No 4 (2018), 2019)
Avian Influenza Disease (AI) has has evolved continuously that impact on economic losses incurred. Deaths can reach 90% -100%. AI’s prevention strategies one of them is a vaccinations. AI vaccine design choice is important for breeders in accordance with the needs and the field. This research aims to analyze poultry farmer preference to AI vaccine product design. Data analysis using descriptive tabulation and Descrete Choice Experiment (DCE) followed regression of multinominal logit to look for influencing variables. The results showed that farmer preference to AI vaccine choice isvaccine design model (F) 28%,vaccine (D) 23%, vaccine (E) 22%, vaccine (C) 16%, vaccine (B) 8% and vaccine (A) 3%.Vaccine (F) is predominantly a breeder preference where has the highest level of category combinations. Variables that have answers to design decisions are vaccine design (D) design solutions and services (D), options for vaccine selection (E), and vaccine selection service (B). Breeders in vaccine selection are more concerned with quality variables and who provide laboratory services because they are a major factor in the success of vaccination programs.